In the Time of COVID-19: The Bojjhaṅgas—Chant Them if You Wish, but Applying Them Is Even Better - Kanyanadhammo (Chandaphol), Phra Nattanachai; Kittiwanno, Phrakhru Baitikawieng (Journal of Buddhist Education and Research (JBER), 2026)
The book entitled “In the Time of COVID-19: Bojjhaṅga—Chanting Is Good, but Practicing Is Better” was written by Somdet Phra Buddhaghosacariya (P.A. Payutto) and published in 2020. The book consists of 50 pages and focuses on the role of the mind in coping with crises. It discusses the question of why monks are invited to chant the Bojjhaṅga Sutta and how such chanting may contribute to healing illness. The author explains that, at the most fundamental level, the practice should be understood as an expression of goodwill and compassion, reflecting the sincere wish that all individuals and society as a whole may overcome difficult and adverse circumstances safely and peacefully. The reviewer chose this book because the COVID-19 pandemic created numerous challenges for Thai society, including political, administrative, public health, and economic problems. These difficulties affected people’s livelihoods, employment, living conditions, access to food, and medical treatment. In such a period of crisis, one of the most important sources of strength is the human mind. The reviewer believes that Buddhist teachings can serve as a valuable spiritual anchor, helping individuals maintain inner stability and resilience. By applying Buddhist principles in daily life, people can cultivate wisdom, peace of mind, and well-being, enabling them to navigate hardships and pursue lasting happiness.